Pengaruh Lingkungan Digital terhadap Interaksi Sosial dan Perkembangan Emosional Murid MI/SD: Sebuah Kajian Literasi Digital - Uci Purnama Sari; Selvia Lestari; Elisa Fitri; Yasmin Nur Anisah; Habeb Saputra (CV. ITTC INDONESIA, 2026)
The rapid development of digital technology has significantly changed the lives of elementary school children, particularly in terms of social interaction and emotional development. High gadget usage without proper supervision may reduce the quality of social interaction and affect children’s emotional stability. This study aims to analyze the influence of the digital environment on children’s social interaction and emotional development from a digital literacy perspective. This research employs a literature review method by examining various relevant sources, including national and international journals, books, and research reports published between 2020 and 2024. The data were analyzed using thematic and narrative analysis techniques to identify patterns of positive and negative impacts of digital technology on children. The findings show that the digital environment has dual effects. Positively, digital technology enhances creativity, strengthens digital literacy skills, and supports more interactive and engaging learning processes. However, excessive and uncontrolled use may reduce face-to-face interaction, weaken empathy, and lead to difficulties in emotional regulation such as irritability, impatience, and impulsive behavior. Therefore, active roles of parents and teachers are essential in supervising technology use, limiting screen time, and balancing digital activities with real-life social interactions to ensure optimal child development.